Estudo da adsorção de atrazina e carbendazim em biocarvão ativado produzido a partir da pirólise da palha de milho - Nascimento, Cleuciane Tillvitz do (2019)
Innumerous studies have reported the harmful effects of pesticides on human and animal health. The presence of pesticides atrazine and carbendazim are associated with the development of various types of cancer and infertility. The objective of this work was to evaluate the adsorption of the pesticides, atrazine and carbendazim onto biochar produced from pyrolysis of corn straw. For the production of the biochar, the corn straw was activated with solution of H3PO4 (1.5 mol L-1), and submitted to pyrolysis in a heating furnace with N2 flow at 400 ºC for 6 hours. Kinetic and equilibrium adsorption experiments were performed in closed and batch system for both pesticides. The models of adsorption in the adsorbent sites, film diffusion and intraparticle diffusion were applied for the modelling of the kinetics data. Physical-chemical, textural and morphological characterization of activated and non-activated corn straw and the activated biochar produce, were performed. Breakthrough curves for the adsorption of atrazine in fixed bed column under different feed flow rate and bed height, were obtained using a phenomenological mathematic modelling (LDF model) associated to a CCD experimental design. The TGA analysis of non-activated corn straw showed a very characteristic profile related to degradation of lignocellulosic material in biomasses. TGA for activated corn straw showed a faster degradation when compared with the non-activated corn straw. The N2 physisorption analysis for activated biochar from corn straw provided surface area, total pore volume and mean pore diameter of 158 m2 g-1, 0.0960 cm3 g-1 and 17.6 Å, respectively. The FTIR analysis for activated biochar indicated the presence of functional groups related to aliphatic and aromatic carbonic structures present on the surface of the material. The pHZPC of the activated biochar produced was estimated at 5.11. The micrographs obtained from MEV showed a greater porosity of the activated biochar. Adsorption equilibrium data for pesticides showed favorable adsorption processes, where, Langmuir isotherm described the systems investigated. The kinetics adsorption data of the pesticides were obtained for different initial concentrations solutions (10, 20 and 30 mg L-1), where, very similar equilibrium times were observed (600 to 900 minutes). The adsorption capacity of atrazine was 20.6, 25.3 e 22.06 mg g-1 for initial concentrations of 10, 20 and 30 mg L-1, respectively, while for the carbendazim was 9.44, 21.1 e 34.7 mg g-1. In the description of adsorption kinetics, the intraparticle diffusion model fitted well the experimental data in the three initial concentrations of atrazine and carbendazim used, providing values of intraparticle diffusion coefficient (Def) in the magnitude of 10-7 to 10-8 cm² min-1. For the study of atrazine adsorption in fixed bed column, the maximization of efficiency column according with the investigated variables was obtained for feed flow rate of 2.5 mL min-1 and bed height of 13.5 cm, in which, the experimental efficiency was 65 %. The results showed the effectiveness of the biochar from corn straw in the removal of atrazine and carbendazim from liquid phase. The performance of this adsorbent makes it promising in the removal of these pesticides from drinking water.